2019
DOI: 10.1111/ggi.13763
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical impact of snoring in older community‐dwelling adults

Abstract: Aim The prevalence and clinical impact of snoring in the independent older adult population is unknown. To address this, we carried out this cross‐sectional epidemiological study of community‐dwelling independent older adults. Methods The study data were collected by the Japan Gerontological Evaluation Study 2013, a postal survey distributed to a large cohort of independent community‐dwelling older adults (aged ≥65 years) in 2013, across 30 municipalities of 14 prefectures. We used data for 24 837 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In a study of Japanese seniors aged ≥65 years, it was discovered that women with elevated snoring frequency had a higher risk of diabetes, whereas this correlation was only seen in men without obesity. 22 The preceding study enrolled only older adults, whereas our study included individuals aged 30–79 years and found comparable results after age adjustment. Our analysis also controlled for abdominal obesity and body mass index in women, and the snoring-diabetes association remained strong.…”
Section: Discussionsupporting
confidence: 50%
“…In a study of Japanese seniors aged ≥65 years, it was discovered that women with elevated snoring frequency had a higher risk of diabetes, whereas this correlation was only seen in men without obesity. 22 The preceding study enrolled only older adults, whereas our study included individuals aged 30–79 years and found comparable results after age adjustment. Our analysis also controlled for abdominal obesity and body mass index in women, and the snoring-diabetes association remained strong.…”
Section: Discussionsupporting
confidence: 50%
“… 3 Snoring is associated with hypertension, diabetes, and heart disease in elderly patients. 4 Most research has noted an increasing trend of snoring among younger generations (aged 30–50 years) as well as older ones (aged >65 years). 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%